Assembly and dynamic regulation of the tip filament of the Bordetella type III secretion system injectisome - Malcova, Ivana; Zmuda, Martin; Valecka, Jan; Kamanova, Jana (mBio, 2025)
UNLABELLED: Many gram-negative bacteria utilize a type III secretion system (T3SS) injectisome to translocate effector proteins directly into host cells. In Bordetella bronchiseptica, a respiratory pathogen of diverse mammals, the T3SS injectisome contains a unique needle tip filament formed by the Bsp22 protein, which is essential for bacterial persistence in mice. Here, we used B. bronchiseptica and Bordetella pertussis strains with in-frame insertions of peptide tags into Bsp22 to investigate filament formation using super-resolution imaging with fluorophore-labeled nanobodies and biarsenic probes. During cultivation on glass coverslips, more than 50% of the bacteria had flexible Bsp22 filaments with an average length of 1 µm after 3 hours of incubation. Filament growth occurred continuously at the distal end. In contrast, during HeLa cell infection, although the T3SS effector BteA was delivered into host cells and the number of filaments per bacterium remained unchanged, filament length was significantly shorter, averaging 0.4 µm after 3 hours of infection. Some Bsp22 filaments formed short physical bridges between bacteria and host cells. During infection of nasal epithelial cells in air-liquid interface cultures, Bsp22 filaments became scarce, with most bacteria lacking detectable filaments. This reduction correlated with a specific decline in bsp22 mRNA levels, while mRNA levels of bscD, encoding the inner membrane ring component of the injectisome, remained stable. Our findings demonstrate that Bsp22 synthesis is tightly regulated in response to environmental cues and highlight how filament characteristics of Bordetella T3SS injectisome change in different environments. IMPORTANCE: Bordetella bronchiseptica and Bordetella pertussis are two closely related respiratory pathogens that employ their T3SS injectisome to deliver the BteA effector into host cells. In this study, we visualized the needle tip filament of their T3SS injectisome, a structure formed by the Bsp22 protein. We demonstrate that during Bordetella cultivation in Stainer-Scholte medium, Bsp22 filaments are abundant and can dynamically extend up to several micrometers in length through the incorporation of new subunits at their distal ends. In contrast, these filaments become shorter and/or less abundant during infection of host cells. This reduction correlates with decreased bsp22 mRNA expression and lower Bsp22 protein levels, while the levels of bscD mRNA, which encodes the inner membrane ring protein of the injectisome, remain stable. These results highlight the adaptability of the Bordetella T3SS injectisome and show how its tip filament structure changes in response to different environments.
Keywords: Virulence Factors, Bordetella; needle tip filament; Bordetella pertussis; regulace genové exprese u bakterií; lidé; Type III Secretion Systems; Bsp22; Epithelial Cells; bakteriální proteiny; EspA; Bordetella bronchiseptica; Gene Expression Regulation, Bacterial; Humans; HeLa buňky; HeLa Cells; tip protein; Bacterial Proteins; epitelové buňky; type III secretion system; sekreční systém typu III; faktory virulence rodu Bordetella; Bordetella